Women in Australian Pentecostalism: Leadership, Submission, and Feminism in Hillsong Church - Miller, Elizabeth (Journal for the academic study of religion, 2016)
Women were highly active participants in, and often leaders of, early Pentecostal churches. While Pentecostalism remains attractive to women who continue to be numerically overrepresented among the lay population of churches, rates of female leadership have declined. This article explores the gendered dimensions of Australian Pentecostalism using Hillsong Church, and particularly its Colour Conferences, as a case study. It considers the historic position of women in the Pentecostal movement and in Australian Pentecostal and Charismatic Churches--with an emphasis on women as leaders--before exploring contemporary gender dynamics in these churches, the ways they have been articulated by church leaders, both male and female, and Pentecostal responses to feminism. It argues that while Pentecostal and Charismatic women in Australia have experienced broad social changes that have transformed their lives and the ways they participate in wider society over the past century, their roles within their churches have not similarly changed. A theology of submission constrains the power Pentecostal women have and the roles they play both in their church and in society.